2009
DOI: 10.1152/japplphysiol.90872.2008
|View full text |Cite
|
Sign up to set email alerts
|

Endurance exercise activates matrix metalloproteinases in human skeletal muscle

Abstract: Rullman E, Norrbom J, Strö mberg A, Wå gsä ter D, Rundqvist H, Haas T, Gustafsson T. Endurance exercise activates matrix metalloproteinases in human skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
110
3
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(132 citation statements)
references
References 34 publications
13
110
3
6
Order By: Relevance
“…For example, tenocytes in silicone micropillar gels elevate MMP expression levels in response to gel deformation (Maeda et al, 2013). In addition, humans show dramatic increases in the levels of MMP2, MMP9 and MMP14 in adult tendons following endurance exercise, suggesting that these proteins aid MTJ repair in response to mechanotransduction (Rullman et al, 2009). This effect depends on the timing of loading as, in cultured tendon fascicles, cells upregulate MMP2 and MMP13 after very short cycles of loading, but downregulate MMP1 after longer cycles (Maeda et al, 2009(Maeda et al, , 2013.…”
Section: Mechanical Forces and Signalingmentioning
confidence: 99%
“…For example, tenocytes in silicone micropillar gels elevate MMP expression levels in response to gel deformation (Maeda et al, 2013). In addition, humans show dramatic increases in the levels of MMP2, MMP9 and MMP14 in adult tendons following endurance exercise, suggesting that these proteins aid MTJ repair in response to mechanotransduction (Rullman et al, 2009). This effect depends on the timing of loading as, in cultured tendon fascicles, cells upregulate MMP2 and MMP13 after very short cycles of loading, but downregulate MMP1 after longer cycles (Maeda et al, 2009(Maeda et al, , 2013.…”
Section: Mechanical Forces and Signalingmentioning
confidence: 99%
“…18 Endurance exercise training has been shown to affect MMP messenger RNA (mRNA), protein and activity in human skeletal muscle. 19 Exercise exerts an effect on MMPs due to multiple potential stimulating factors, such as mechanical loading, 20 local ischaemia 21 and tensile forces in the muscle. 22,23 Exercise-induced angiogenesis requires MMP degradation of the ECM in order to allow for endothelial sprouting.…”
Section: Introductionmentioning
confidence: 99%
“…This difference reflects the impact of exercise training and may be associated with an inflammatory response (61). Rullman et al (62) reported that endurance exercise enhances MMP-9 but not MMP-2 levels in human skeletal muscle in healthy subjects.…”
mentioning
confidence: 99%